Genetic landscape of Segawa disease in Spain. Long-term treatment outcomes. (January 2022) - Fernández-Ramos, Joaquín A.; De la Torre-Aguilar, María José; Quintáns, Beatriz; Pérez-Navero, Juan Luis; Beyer, Katrin; López-Laso, Eduardo; ,; Ochoa Sepúlveda, J.J.; Serrano Cárdenas, J.; Sobrido Gómez, M.J.; Mora, M.D.; Moreno-Medinilla, E.; et al.
Abstract: Introduction: In 2009, we described a possible founder effect of autosomal dominant Segawa disease in Córdoba (Spain) due to mutation c.265C>T (p. Q89*) in the GCH1 gene. We present a retrospective multicentre study aimed at improving our knowledge of Segawa disease in Spain and providing a detailed phenotypic-genotypic description of patients. Methods: Clinical-genetic information were obtained from standardized questionnaires that were completed by the neurologists attending children and/or adults from 16 Spanish hospitals. Results: Eighty subjects belonging to 24 pedigrees had heterozygous mutations in GCH1 . Seven genetic variants have been described only in our cohort of patients, 5 of which are novel mutations. Five families not previously described with p. Q89* were detected in Andalusia due to a possible founder effect. The median latency to diagnosis was 5 years (IQR 0–16). The most frequent signs and/or symptoms were lower limb dystonia (38/56, 67.8%, p = 0.008) and diurnal fluctuations (38/56, 67.8%, p = 0.008). Diurnal fluctuations were not present in the phenotypes other than dystonia. Fifty-three of 56 symptomatic patients were treated with a levodopa/decarboxylase inhibitor for (mean ± SD) 12.4 ± 8.12 years, with 81% at doses lower than 350 mg/day (≤5 mg/kg/d in children). Eleven of 53 (20%) patients had nonresponsive symptoms that affected daily life activities. Dyskinesias (4 subjects) were the most prominent adverse effects. Conclusion: This study identifies 5 novel mutations and supports the hypothesis of a founder effect of p. Q89* in Andalusia. New insights are provided for the phenotypes and long-term treatment responses, which may improve early recognition and therapeutic management. Highlights: Five genetic changes were found for the first time in Segawa disease. Seven genetic changes were described only in our cohort. Five novel families with the founder mutation p. Q89* were found in Andalusia. Diurnal fluctuations characterized dystonia but not the other phenotypes. Twenty percent of patients had levodopa nonresponsive symptoms that affected daily life.